Home Market and Traditional Effects on Comparative Advantage in a Gravity Approach - Dieter Schumacher (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
Policy makers in "small" countries facing trade liberalisation have become concerned with the potential loss of manufacturing employment and output to "large" economies in the presence of economies of scale in production and international transport costs. This paper offers a methodology to estimate the "home market" effect for numerous industries, after accounting for transport costs and traditional comparative advantage effects. The empirical results suggest significant home-market effects in many manufacturing industries which may be capital intensive or labour intensive.
Keywords: F12; 330; Home-market effect; comparative advantage; bilateral trade; factor endowment; gravity model; Komparativer Kostenvorteil; Internationale Wirtschaftsbeziehungen; Gravitationsmodell; Schätzung; Theorie; OECD-Staaten; home market effect